Від Холуя до Холуйства - Поповський, Анатолій (Видавництво Львівської політехніки, 2017)
The article considers the etymology, lexical and semantic features and word-building functions of the word "kholui" in texts of literary, publicistic, scientific and official styles.
Keywords: етимологія; синоніми; семантика; словотвір; номінація; антропоніми; експресія; метонімія; епітет; метафора